Comparison Study between FEM Simulation and Experimental of Heat and Mass Transfer in Kek Lapis Sarawak Baking - Z. Abidin, A. S.; Hamsawi, M. S.; Rigit, A.R.H.; Zafwan, M. S.; Mohamaddan, S.; Muslimen, R.; Annisa, J.; Junaidi, N. (International Journal of Integrated Engineering, 2018)
Kek Lapis Sarawak is specialty dish from Sarawak. Kek Lapis Sarawak industry contributes a lot to the state’s economy. In cake industry, the use of oven in the baking process contributes to high energy consumption. Nowadays, energy has become an operational issue and there is a need to minimize energy consumption to reduce production cost. This research aims to optimize the baking process for an efficient energy consumption. Therefore, it is important to investigate the relationship between baking temperature, time and cake quality. Accurate temperature and time will define an efficient baking process. Kek Lapis Sarawak baking process has been modelled and simulated using finite element method (FEM). Results from the model was validated with an experiment. There is specific oven temperature needed to enable perfect gelatinization and coagulation to happen which is 190 °C. While baking time are varied by layers. The baking time is reducing as more layers added.  The finding shows interdependent relationship between porosity, thermal conductivity and moisture content where higher porosity  can lead to poor thermal conductivity.